Landscape Effects on Native Bees (Hymenoptera: Anthophila) Captured in Pheromone Traps for Noctuid Crop Pests (Lepidoptera: Noctuidae). Issue 4 (7th May 2021) - Parys, Katherine A; Elkins, Blake H; Little, Nathan S; Allen, K Clint; Crow, Whitney; Cook, Don; Wright, Karen W; Zhu, Yu Cheng; Griswold, Terry
Abstract: Noctuid pests, including tobacco budworm ( Chloridea virescens (Fab.)) and bollworm ( Helicoverpa zea (Boddie)), are significant pests of southern row crops including cotton ( Gossypium hirsutum L.), corn ( Zea mays L.), and soybean ( Glycine max (L.) Moench.). This pest complex is seasonally monitored through Hartstack traps that are baited with synthetic lepidopteran pheromones across the southern United States. We examined bycatch from the noctuid traps deployed across the Mississippi Delta in 2015, 2016, and 2017 for the presence of bees. The most abundant species collected were honey bees ( Apis mellifera L.), bumble bees ( Bombus spp.), and long-horned bees ( Melissodes spp.); these three genera accounted for 82.4% of specimens collected. We also evaluated the proportion of local- and landscape-level habitats on the abundance and richness of the bees caught as bycatch. The proportion of natural and semi-natural habitat affected the abundance and richness of bees collected at the landscape level, but not at more local scales. Additional research is needed to better understand these interactions between bycatch and landscape factors to minimize non-target collections.